Image and propaganda in the religious conflicts of the 16th and 17th centuries: from the Spanish fury to the plundering of Magdeburg and Tirlemont - Retortillo Atienza, Asuncion; Soto de Prado Otero, Catalina; Borreguero Beltrán, Cristina (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2018)
This work aims to show the strength of propaganda in the religious conflicts of the late 16th and first half of the 17th century through the many images that have survived. The rulers, particularly Protestants, sharpened their skillful propaganda machinery using the image as a fundamental element for the creation of an "Antihabsburg" visual culture. The brutality of looting was especially used as a thrown weapon to shape European "public opinion" against enemy States and armies. The analysis of films and engravings of the time, as well as of the literature, reveals not only the deliberate construction of a propaganda, but also of myths, stereotyped visions and national clichés that are still repeated today.